2000
DOI: 10.1080/080394800448147
|View full text |Cite
|
Sign up to set email alerts
|

Violence in a Finnish forensic psychiatric hospital

Abstract: HJO. Violence in a Finnish forensic psychiatric hospital. Nord J Psychiatry 2000;54:269-273. Oslo. ISSN 0803-9488.A study of the number, perpetrator, time and target of violent behaviour was carried out in a Finnish state forensic psychiatric hospital, Vanha Vaasa Hospital -Gamla Vasa Sjukhus. Forensic psychiatric patients and patients difficult-to-treat are treated in the hospital. According to the results the number of violent incidents has been quite small in the hospital during the time of the study in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
21
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
9
21
2
Order By: Relevance
“…First, we replicated the observation that a small subgroup of individuals are involved in a large number of violent episodes in the inpatient setting (e.g., Chang & Lee, 2004;Decaire et al, 2006;Kraus & Sheitman, 2004;Owen et al, 1998;Weizmann-Henelius & Suutala, 2000). The proportion of patients identified as CVPs (i.e., 1.4% to 21.1%) has varied greatly in prior investigations mainly because of methodological and sampling differences across studies.…”
Section: The Base Rate Of Chronic Violence During Inpatient Treatmentmentioning
confidence: 87%
See 2 more Smart Citations
“…First, we replicated the observation that a small subgroup of individuals are involved in a large number of violent episodes in the inpatient setting (e.g., Chang & Lee, 2004;Decaire et al, 2006;Kraus & Sheitman, 2004;Owen et al, 1998;Weizmann-Henelius & Suutala, 2000). The proportion of patients identified as CVPs (i.e., 1.4% to 21.1%) has varied greatly in prior investigations mainly because of methodological and sampling differences across studies.…”
Section: The Base Rate Of Chronic Violence During Inpatient Treatmentmentioning
confidence: 87%
“…J. Cooper et al, 1983;Decaire et al, 2006;Tam et al, 1996;Weizmann-Henelius & Suutala, 2000). CVPs were involved in more than 60% of all recorded violent episodes during the 1-year study period.…”
Section: The Base Rate Of Chronic Violence During Inpatient Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…), and in a study of general psychiatric patients; one third of the physically violent patients were female (Ogloff & Daffern ). It was reported previously from the other forensic psychiatric hospital in Finland that female patients caused three fourths of violent incidents (Weizmann‐Henelius & Suutala ). In the present study, female patients caused only one fourth of the incidents.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that only a minority of mental patients generates the majority of institutional violence (Weizmann‐Henelius & Suutala , Almvik et al . , Lussier et al .…”
Section: Introductionmentioning
confidence: 99%